Factors Affecting the Academic and Co-Curricular Performance of Muslim Pupils in San Jose Elementary School - Glofel Adra Prada (2015)
The study aimed to determine the factors affecting the academic and co-curricular performance of Muslim pupils in San Jose Elementary School, Rodriguez, Rizal during the School Year 2014-2015 in terms of personal-related factors, parents participation-related factors, teacher related factor, and school-related factors. The study utilized the descriptive-qualitative and descriptive survey design.
GS Thesis